Coal and Gas Comining in the High-Gas Detong Mine, China: Analytical and Numerical Parameter Optimization of Gas Extraction Boreholes - Wei Wang; Zongxiang Li; Guangmin Zhao; Yujin Chen (Advances in Civil Engineering)
The upper corner gas overrun caused by goaf gas gushing in the high-gas mine can be mitigated by roof positioning of long boreholes in the goaf fracture zone, creating an artificial gas migration channel and achieving safe comining of coal and gas. This study numerically simulated the fracture evolution in the coal rock overlying goaf in workface #2-104 of the Detong Mine, China. Using the O-shaped circle theory and the FLAC3D commercial software package, the range parameters of goaf fracture zone gas-concentrated areas were obtained by defining the pressure relief coefficient, which provided a basis for the arrangement of holes in the goaf located at 15 m from the workface goaf collapse zone to the workface floor and 15–60 m from the structure zone to the workface. According to the obtained goaf parameters, the distribution and migration law in the goaf under the conditions of initial state and extraction with different roof borehole parameters were simulated by the FLUENT software. The optimal borehole location was 30 m from the floor and 25 m from the return airway. The field experiment with three boreholes arranged in the optimal extraction position provided the extraction concentration in the borehole above 30%, the gas extraction volume of 12 m3·min−1, and the concentration at the upper corner below 1%, which ensured safe coal and gas comining.